Docências em escolas de fronteira: diferenças, silenciamentos e possibilidades de pedagogias interculturais - Oliveira, Joelma Fernandes de (Universidade do Vale do Rio dos Sinos, 2019)
This thesis presents a analysis about teaching in Border Schools, at the state of Roraima. The goals stood for: a) to research how are presented different kinds of teaching in this specific Border School, verifying pedagogical practices and cultural relations stablished within such a space; b) to cognize the pedagogical practices that circulate in this school; and c) to analyze the curriculum of the school under study since it is located in a frontier region (Brazil/Venezuela). The theoretical-methodological approach presents a qualitative nature, employing registered notations from Field Journal and a semistructured interview script, counting with 2 (two) pedagogical coordinators and 8 (eight) teachers from different knowledge areas. Concerning methodology material analysis, it was also resorted to a content analysis, in order to contemplate the empirical data produced during the research. The results exhibit that, on the Border School under analysis, a sort of teaching is identified, on the one hand, as perceiving cultural differences as specificities to be considered for development of teaching and learning at school; on the other hand, there is also a kind of teaching that promotes invisibility of some subjects from that space, mainly non-Brazilians. At the end of this investigation, it was possible to sustain the following thesis: Border Schools consist of space for wide, distinct, multiple and complex cultural relations. When teaching arranges possibilities for learning and teaching, there is teaching for the differences; when teaching, however, does not intend to see the problems nor to arrange possibilities for learning and teaching, there is teaching of invisibility, that is, that prohibit and do not realize the other of the difference. All of this lead to conclude that contemporary teaching, both in the specificity of a Border School and in Education as a whole, refer to the relationship with differences, which are potentiated and produced in relation to the Other.
Keywords: Diferenças; Docências; Escolas de fronteira; Relações culturais; Differences; Teaching; Border schools; Cultural relations; ACCNPQ::Ciências Humanas::Educação